Hubungan antara penalaran moral dan iklim sekolah dengan perilaku bullying - Munir Rotun; Awalya Awalya (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
The purpose of this research was to determine the relationship between moral reasoning and school climate with bullying behavior in class XI students of SMK Negeri 1 Ponorogo. The study population was all students of class XI and the sample amounted to 207 students who were divided into each class in all class XI. The measuring instrument uses a psychological scale of moral reasoning, a psychological scale of school climate and a psychological scale of bullying behavior. The results of this study indicate that there is a significant relationship between moral reasoning and school climate with bullying behavior among students of SMK Negeri 1 Ponorogo (p = 0.015) (R = 0.537) (F = 0.288). So that overall it can be concluded that the lower the moral reasoning, the higher the student's bullying behavior, the higher the school climate, the lower the student's bullying behavior, and the higher the moral reasoning and the school climate, the lower the student's bullying behavior.